Influence of hygroscopic expansion of clay minerals on the dynamic evolution of coal permeability. (15th December 2022) - Yongzan, Wen; Guanhua, Ni; Zhao, Li; Wenzhou, Du; Hui, Wang; Gang, Wang; Zhen, Liu
Highlights: A dynamic evolution model of coal permeability is established. The influence of clay minerals on permeability is put forward. Experiment and simulation confirm each other. Influence of moisture absorption expansion on coal stress. Abstract: Exploring the evolution characteristics of hygroscopic expansion of clay minerals in coal on its permeability has a positive effect on improving coal seam permeability. Firstly, the dynamic evolution model of coal permeability affected by hygroscopic expansion was established. Secondly, numerical simulation is carried out after an adaptive multi-field multiphase coupling tester verifies the model. Finally, the evolution law of coal permeability under different confining pressures and different moisture absorption expansion coefficients is analyzed. Research shows that the permeability of coal samples decreases first and then increases with the stress in the shape of a deep "V". Due to the hydration and softening of clay minerals caused by hygroscopic expansion, the peak stress and permeability decreased by 3.8% and 1.69%, respectively, and the plastic strain increased by 6%. In this process, the change of permeability of axially compressed coal samples plays a leading role. Before reaching the yield stress, the influence of hygroscopic expansion on the change of permeability of the coal sample is more obvious. The research results enrich the theory of permeability dynamic evolution and have great significance in guiding coalbed methane exploitation.